Analisis Pengaruh Faktor Operasional terhadap Waktu Tunggu Kapal di Pelabuhan Curah - Romulo Sitorus; Andar Sri Sumantri; Sulistyowati Sulistyowati (Indonesian Maritime Researchers and Lecturers, 2025)
This quantitative study analyzes the influence of Ship Docking Schedule (X1), Port Availability (X2), and Loading and Unloading Productivity (X3) on Vessel Waiting Time (Y) at Tanjung Intan Cilacap Port. Data were collected through questionnaires administered to 86 vessel crew respondents and analyzed using Multiple Linear Regression (SPSS v.26). The t-test results indicate that X1, X2, and X3 individually exert a positive and significant influence on Y.1 The regression model demonstrates robust predictive power, explaining 55.2% of the variance in vessel waiting time (R^2adj=0.552). Based on the standardized beta coefficients, the Ship Docking Schedule (X1, β=0,385) is identified as the most dominant factor, followed by Loading and Unloading Productivity (X3, β=0,302) and Port Availability (X2, β=0,307).1 This finding confirms that optimizing maritime logistics performance, particularly in bulk terminals facing physical constraints, requires prioritizing procedural efficiency and scheduling accuracy.